Nanoemulsion Formulation and Evaluation of Terminalia chebula Fruit to Improve Bioavailability - Panchabudhe, Dhanshree (Asian Journal of Pharmaceutics (AJP), 2025)
Terminalia chebula is a reputed medicinal plant with various therapeutic characteristics; however, it is limited by poor solubility and permeability, leading to low bioavailability. A novel nanoemulsion-based formulation was developed and evaluated to improve the aforementioned properties. The nanoemulsion was prepared using oil in water method with appropriate surfactants and cosurfactants to increase the solubility and stability of bioactive compounds in T. chebula fruit extract. To explore its properties, the formulation was characterized for parameters such as particle size, zeta potential, polydispersity index, and stability under different conditions. In vitro release studies indicated a considerably enhanced dissolution rate as against that of conventional extracts, the presence of augmented bioavailability was further corroborated through the enhanced pharmacokinetics parameters in the in vivo studies. This approach upholds a real strategy to maximize therapeutic efficacy associated with T. chebula substances, pointing toward their use in developing effective herbal medicine.